Prostatitis No.1 traditional chinese medicine significantly exhibited anti-inflammation role on prostatitis through miR-205-5p/YES1: Anti-inflammation role on prostatitis through miR-205-5p/YES1 - Liu, Jia; Fan, Yongchao; Song, Ruiyu; Tian, Zhaohui; Yan, Baofei; Ma, Yuting; Zeng, Qingqi (Cellular and Molecular Biology, 2023)
Prostatitis is one common male disease with a high prevalence. Traditional Chinese medicine (TCM) has been used as an alternative method for the treatment. However, the molecular mechanism of Prostatitis No.1 Traditional Chinese Medicine (P1TCM) on prostatitis is still unclear. For this purpose, the rat models were constructed and treated with PITCM of control, model, low (10 g/kg/d), medium (20 g/kg/d), and high (40 g/kg/d), as well as the transfections of medium dosage+NC mimic, and medium dosage+miR-205-5p mimic, medium dosage+NC mimic+pc-NC, medium dosage+miR-205-5p mimic+pc-NC, and medium dosage+miR-205-5p mimic+pc-v-YES-1 Yamaguchi sarcoma viral oncogene homolog 1 (YES1). Real-time quantitative PCR (qPCR) and western blotting analyses were carried out to evaluate the expression of miR-205-5p and YES1, respectively. The levels of interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) were assessed by enzyme-linked immunosorbent assay (ELISA). The targeting role of miR-205-5p on YES1 was predicted by StarBase and verified by a dual-luciferase reporter gene assay. Results showed that the optimal treatment of P1TCM relieved the damage of prostate tissue, decreased the immunity and inflammation factors, and reduced the expression level of miR-205-5p in prostate tissue and serum. miR-205-5p mimics significantly relieved tissue damage and reduced immunity and inflammatory functions. miR-205-5p targeted YES1. YES1 was significantly upregulated in medium dosage treatment compared with Control, while downregulated compared with the Model. YES1 was also upregulated in prostatitis patients. The pc-YES1 reversed the function of the miR-205-5p mimic. In conclusion, P1TCM significantly relieved the tissue damage and reduced prostate patients’ inflammatory functions through miR-205-5p/YES1, which might be essential for clinical studies.